Prevalence of Catheter-associated bacteriuria in patients who received short-term catheterization in the northeast of Iran - Khaledi, Azad; Hooshyar Chichaklu, Amin; Piroozmand, Ahmad; Meskini, Maryam; Ghazvini, Kiarash (Novelty in Biomedicine, 2018)
Background: Catheter-associated (CA) bacteriuria is a result of the extensive usage of urinary catheterization. Once a catheter is placed, many patients achieve bacteriuria, even with the use of greatest consideration and care of the catheter. In this study, we decided to evaluate the prevalence of Catheter-associated bacteriuria in patients who received short-term catheterization in the northeast of Iran. Materials and Methods: In this cross-sectional study during one year (among 2014-2015) 275 patients who have admitted recently and have no history of catheterization and drug consumption were included. Three samples were taken from patients before, one day after catheterization and after removal of the catheter. The urine samples were analyzed and cultured on the suitable media. Antibiotics susceptibility testing was performed by disk diffusion method. Then, data analyzed using SPSS software by Student t-test. In addition, the p values less than 0.05 were considered as significant. Results: In general, the rate of catheter-associated bacteriuria in these hospitals was 68% (187 cases of 275). The mean age of the participants and patients with bacteriuria were 41±1.2 and 24.8±6.2 years old, respectively. The most common isolated bacteria were Escherichia coli (50.6%) followed by Staphylococcus aureus and Klebsiella pneumonia (21.6%). The highest sensitivity was reported against kanamycin (68.9%) and highest resistance was observed against ampicillin with a rate of 96.3%. Conclusion: For prevention of healthcare-associated UTI, correct catheterization and use of the closed catheter system is recommended. In addition, before prescribing any antibiotics it should be paying attention to the antibiotics susceptibility testing results.